1992
DOI: 10.1897/1552-8618(1992)11[1635:eobkme]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bleached Kraft Mill Effluent on Fish in the St. Maurice River, Quebec

Abstract: Tissue levels of chlorinated dioxins and furans and the physiological and biochemical responses of fish were measured upstream and downstream of a bleached kraft mill in the St. Maurice River, Quebec. Relative to fish 10 km upstream of the source, white suckers (Catostomus commersoni) downstream showed evidence of chemical exposure, chemical metabolism, stress, and altered energy use. Levels of 2,3,7,8–tetrachlorodibenzo‐p‐dioxin and tetrachlorodibenzofuran in gutted whole fish averaged 23 and 260 pg/g immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 32 publications
6
72
1
Order By: Relevance
“…Similar observations were made by Hodson et al (1992) In order to study the impact of these heavy metals on histopathology, three organs, i.e.…”
Section: Accepted Manuscriptsupporting
confidence: 55%
“…Similar observations were made by Hodson et al (1992) In order to study the impact of these heavy metals on histopathology, three organs, i.e.…”
Section: Accepted Manuscriptsupporting
confidence: 55%
“…Mountain whitefish (Prosopium williamsoni) had significantly higher levels of EROD induction than longnose suckers (Catostomus catostomus) or burbot (Lota lota) collected from the same sites (Kloepper-Sams and Benton 1994). In another study on the St. Maurice River in Quebec, hepatic aryl hydrocarbon hydrolase (AHH) of white suckers (Catostomus commersoni) was more sensitive to induction than that of the predatory northern pike (Esox lucius) taken from the same site (Hodson et al 1992). Differences in hepatic P450 activity may be caused by differences in chemical uptake or accumulation owing to feeding differences and proximity of sediments where inducing agents may be located.…”
Section: Discussionmentioning
confidence: 98%
“…Expression of the biotransformation enzyme system cytochrome P450 1A (CYP1A) and body burdens of planar aromatic compounds, such as polynuclear aromatic hydrocarbons, have been observed to be directly related in several field studies (Varanasi et al 1986;Collier et al 1992aCollier et al , 1995. Likewise, many studies examining residual levels of chlorinated dibenzodioxins and furans have shown a direct correlation with CYP1A activity (Hodson et al 1992;Gagnon et al 1994b;. Several of these studies have also documented relationships between CYP1A activity and reproductive effects (Andersson et al 1988;Norrgren et al 1993;Gagnon et al 1994a) as well as hepatic neoplasms (Fabacher and Baumann 1985;Collier et al 1992b).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this same increase was observed, for example, in fish (Catostomus commersoni) living downstream from a pulp and paper mill. These fishes also exhibited several metabolic alterations (including monooxygenase enzyme alterations), delayed age and increased size at maturity, smaller gonads and low fecundity (Hodson et al, 1992;Gagnon et al, 1995).…”
Section: Biological Response and Exposurementioning
confidence: 99%